Third Tier Thinking and Subtle Consciousness - Rowan, John (Journal for the Study of Spirituality, 2012)
We are becoming familiar with the ideas of first tier and second tier thinking from the work of Don Beck, Chris Cowan and Ken Wilber, but little has been written about third tier thinking, which is mentioned briefly by Wilber. It seems that the time has come to give it some consideration, and this is the purpose of this discussion item.